Pitch and torque control of variable speed wind turbines - Kulka, Arkadiusz (My University, 2004)
In this thesis the torque, speed and pitch angle control of variable speed wind turbine is investigated. In particular, it concentrates on the extraction of maximum available energy, reduction of torque and output power variations, which gives stresses in the gearbox and mechanical structure. The control concentrates on separate wind speed internals as well as on whole wind speed region. It is found that the control structures varies substantially between the wind speed regions. Finally the result are compared with measurement made on 2 variable speed turbines.
Keywords: Elkraftteknik; Electric power engineering